The Marriage of Roman Soldiers (13 B.C. - A.D. 235) : Law and Family in the Imperial Army - Phang, Sara Elise (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
In the first and second centuries A.D., Roman soldiers were forbidden legitimate marriage during service: nevertheless, many soldiers formed de facto marriages. This book examines the legal, social, and cultural aspects of the marriage prohibition and soldiers' families. The first section covers the marriage prohibition in Roman literary and legal sources. The second section treats social and legal aspects of the soldiers' families, including a survey of epitaphs, the legal impact of the ban on families, and alternatives to family formation. The final section examines the marriage ban as military policy and its relation to Roman culture. This book will be of interest to scholars of the Roman army, Roman social history, and family law. Students of gender and sexuality in the ancient world will also find it relevant.